Pengaruh Konsentrasi Larutan Garam Dan Lama Fermentasi Terhadap Mutu Kimchi Daun Bawang Lokio - Connie Daniela; Dewi Restuana Sihombing (Jurnal Teknologi dan Mutu Pangan, 2023)
Kimchi is a fermented product made from various types of vegetables with a mixed with seasonings including onions, garlic, and red chili, is believed to offer numerous health benefits. Lokio Cheves are from Batak onion plants which commonly used as medicinal and food ingredient which is abundant in North Sumatera. However, due to its short shelf life, processing the lokio cheves are necessary to extend its shelf life through fermentation process. Given the beneficial properties of kimchi and the abundance of daun bawang lokio, the utilization of this local food source to diversifying kimchi is essential to enhance its benefits and market value. Lactobacillus bacteria which play a role in the fermentation process can produce high levels of lactic acid, enhancing the digestive system's functionality and shelf life. This study aims to investigate the effect of salt solution concentration and fermentation time on the quality of chive chives kimchi. The method of this study used a completely randomized design (CRD) with a two-factor factorial pattern with two repetitions. Factor I was salt concentration 2%;4%;6%; and 8%. Factor II is the fermentation time, 2, 4, 6, 8 (days). The rusults showed, the best treatment was obtained from a salt concentration of 8% with a fermentation time of 2 days resulting in kimchi with total lactic acid bacteria of 2.32 (mg/100g), total dissolved solids of 3.67oBrix, a moisture content of 9.5%, and a pH of 5.17. The best treatment was carried out by antioxidant test, and the antioxidant obtained was 73.4%.